Analyzing a German-language Expanded Form of the PhoPhiKat-45: Psychometric Properties, Factorial Structure, Measurement Invariance with the Likert-Version, and Self-Peer Convergence. Issue 2 (4th March 2021) - Brauer, Kay; Proyer, René T.
Abstract: Personality assessment typically relies on self-report questionnaires utilizing Likert-type scales. Recently, the Expanded format has been proposed as alternative, but research on the consequences of adapting Likert-like responses to Expanded items is sparse. We adapt a multidimensional measure into the Expanded format: the PhoPhiKat-45. This is the standard questionnaire to assess gelotophobia (fear of being laughed at), gelotophilia (joy in being laughed at), and katagelasticism (joy in laughing at others). We test the reliability, item/scale parameters, and factorial structure across the Expanded and Likert formats in three independently collected samples ( N s = 323/261/460). While the psychometric properties are satisfying, elevated item- and mean-scores in our experimental Expanded version do not support full measurement invariance with the Likert version—and, thus, it does not permit the application of established cutoff scores for gelotophobia. The convergence of self-peer ratings supports the validity of an Expanded version. Overall, an Expanded form of the PhoPhiKat-45 did not outperform the standard Likert version. We discuss potential trait- and method-related causes for the measurement invariance and consequences for the usage of cutoff scores in the assessment of gelotophobia as well as interpreting the findings in light of continued research on the Expanded response format.